C-reactive protein and total serum bilirubin as a predictor of perforated appendicitis: a cross sectional study - Pinate, Anil Reddy; R., Shivakumar C.; Shoeb, Mohammad Fazelul Rahman; Patil, Sharangouda (International Surgery Journal, 2018)
Background: C-reactive protein (CRP) and bilirubin have been used as adjuncts for diagnosis of appendicitis. This study assessed the diagnostic value of these markers in patients with suspected acute appendicitis. Methods: CRP values and total serum bilirubin among the patients who presented with acute appendicitis were compared among patients who had perforated appendix and non- perforated appendix. The diagnostic value of CRP and TSB markers as a predictor for perforation were compared in terms of Sensitivity, specificity, PPVs and NPV and the diagnostic accuracy assessed by AUC using receiver operating characteristic (ROC) curve analysis. Results: This study showed sensitivity is 72.50%, specificity of 92.23%, positive predictive value of 78.38% for a raised CRP. The sensitivity of TSB for predicting perforation is 77.50 and the values of specificity, PPV and NPV of the same are 87.38 %, 70.45% and 90.91% respectively. The area under curve was more for CRP than TSB indicating that CRP is better predictor for perforation in appendicitis as compared to the TSB. Conclusions: Thus, serum CRP and total serum bilirubin (TSB) can be used as useful markers for early diagnosis and prediction of perforation in cases of acute appendicitis.